Transfusion practices in the Eastern Cape Province of South Africa in the era of HIV and HAART - Van den Berg, Karin (University of the Free State, 2014)
The HIV/AIDS pandemic has irrevocably changed the face of healthcare delivery and research. This is especially true in South Africa with its estimated 5.26 million HIV-infected people. It was not until the significant up scaling of the anti-retroviral therapy roll-out that the HIV-incidence rate in South Africa started declining substantially from an estimated 1.32% in 2005 to an estimated 0.85% in 2013. Cytopaenias are common in HIV-infected individuals. Their risk of developing anaemia ranges from 60 to 95% during the course of the disease. The impact of HIV/AIDS on blood utilisation in the country is largely unknown. With this study we aimed to address the lack of knowledge regarding the blood requirements of the HIV-positive population and how the changing epidemic may affect future blood utilisation, by establishing what proportion of blood issued to medical and surgical patients admitted to a large referral hospital in the Eastern Cape Province of South Africa, was issued to HIV-positive patients Methods We conducted a retrospective cross-sectional study analysing the prevalence of HIV among patients receiving blood and blood products. Baseline demographic data was collected on all patients admitted during a three-month period with additional clinical data collected on patients who received a blood transfusion. Ethics approval was obtained from the UFS and the South African National Blood Service (SANBS). Approval to complete the study was obtained from the senior management of the Hospital and the local blood service offices. Following a short pilot study during which the various systems were tested, data collection commenced on 7 January 2013 and was completed on 6 April 2013. Results A total of 3438 patient admissions were included in the study with equal distribution between male and female patients. Patients tended to be younger with almost 75% of patients younger than 60. Almost 8% of patients were transfused. HIV status was poorly recorded. Only 25% of patients had a HIV test result on file. The reported HIV prevalence was 14%. The median LOS was 7 days and in-patient mortality 8%. During 330 transfusion episodes, 267 patients received 609 units of RBC, i.e. 1.24 transfusion episodes per patient. Except for 6 units, all units issued were recorded as transfused, translating to a transfused ratio of 1.00:0.99. Being HIV-positive, surgical admissions, having been admitted to ICU, extended LOS and death at discharge were independently association with having received a transfusion. Mean pre- and post-transfusion Hb levels were significantly lower in HIV-positive patients and these patients were less likely to have had a correctly completed consent form on record, but were more likely to have had their anaemia investigated. Discussion The complex HIV-testing at this facility hampered the analysis of the data and raises serious public health questions. Despite this, it is clear that HIV significantly impacts blood utilisation at this facility. HIV-prevalence among all admissions was found to be ~ 14%, as compared to the almost 20% among the recipients of blood. Similarly 26% of the transfusion episodes involved HIV positive patients. However, only 16% of the units issued were issued to HIV-positive patients. The data suggests that HIV-status significantly influenced doctors’ transfusion practices. HIV-positive patients had significantly lower pre- and post-transfusion Hb levels suggesting lower transfusion triggers and targets for HIV-positive patients. These patients were also less likely to have had correctly completed consent forms; only a third of HIV-positive patients had correctly completed forms on record. Conclusion HIV contributes significantly to the blood utilisation at a tertiary hospital in the Eastern Cape and would appear to influence clinicians’ transfusion practice. The exact nature of the interaction between HIV and transfusion requires further investigation.
Keywords: In-hospital mortality; Eastern Cape public health sector; Blood utilisation; Audit of transfusion practices; Anaemia; CD4 count; Antiretroviral drugs; Blood transfusion; HIV/AIDS; Hospitalised patients; Dissertation (M.M. Clinc.Sc. (Transfusion Medicine)--University of Free State, 2014